Partial up and down logic - Jaspars, Jan (1995)
Abstract: "This paper presents logics for reasoning about extension and reduction of partial information states. This enterprise amounts to non-persistent variations of certain constructive logics, in particular the so-called logic of constructible falsity of [Nelson 1949]. We provide simple semantics, sequential calculi, completeness and decidability proofs."
Keywords: Knowledge representation (Information theory)